2017
DOI: 10.1038/s41598-017-06416-4
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/FOXO3/AKT pathway regulates cell death and mediates morphogenetic differentiation of Colorectal Cancer Cells under Simulated Microgravity

Abstract: Gravity is a major physical factor determining the stress and strain around cells. Both in space experiments and ground simulation, change in gravity impacts the viability and function of various types of cells as well as in vivo conditions. Cancer cells have been shown to die under microgravity. This can be exploited for better understanding of the biology and identification of novel avenues for therapeutic intervention. Here, we described the effect of microgravity simulated using Rotational Cell Culture Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 64 publications
3
51
0
Order By: Relevance
“…Microgravity also affects major cellular functions such as cell growth, cell cycle, self-renewal and differentiation 7 , 9 12 . As such, it was hypothesized that microgravity has anticancer potential through cell growth inhibition, and many studies were conducted to investigate this notion 2 , 13 15 . Additionally, microgravity has been reported to cause cellular oxidative stress that leads to the production of reactive oxygen species (ROS), as well as endoplasmic reticulum stress 12 , 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Microgravity also affects major cellular functions such as cell growth, cell cycle, self-renewal and differentiation 7 , 9 12 . As such, it was hypothesized that microgravity has anticancer potential through cell growth inhibition, and many studies were conducted to investigate this notion 2 , 13 15 . Additionally, microgravity has been reported to cause cellular oxidative stress that leads to the production of reactive oxygen species (ROS), as well as endoplasmic reticulum stress 12 , 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the effects of different durations of NG and SMG on various types of cells, ranging from a few seconds to dozens of days, reporting notable effects on different types of cells, including thyroid, colorectal and breast cancer cells (30)(31)(32)(33). In these studies cellular morphology was significantly altered (3D spheroid structure formation and the alteration of the cytoskeleton), the extracellular matrix (ECM) was increased, the cell cycle was modified after 10 and 12 days of SMG (the number of cells in the G 1 phase increased, whilst the number of cells in the S and G /M phases decreased), proliferation capacity was decreased and apoptosis was increased (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a well-established tumor suppressor and increasing studies have suggested it inhibits tumor growth through upregulating FOXO family members such as FOXO3 and FOXO4 [ 37 , 38 ]. In CRC, a recent study have demonstrated that PTEN/FOXO3 signaling cascade induces the growth of CRC cells through regulating cell-cycle related proteins [ 39 ]. CCND1, also known as cyclin D1, is abnormally overexpressed in numerous cancers and promotes uncontrolled tumor growth through influencing cell-cycle progression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%